EFFECT OF TRAINING AND WORK PLACEMENT ON PERFORMANCE (REGIONAL SERVICE, TRAINING AND EDUCATION AGENCY (BKP2D) – INDRAGIRI HULU REGENCY - Yenny Iskandar; Suharmiyati Suharmiyati; Benny Pramana Putra (LPPM Press STIE Indragiri Rengat, 2022)
One of the important factors in the field of human resources is to adapt and create new changes to produce adequate performance towards organizational goals. To achieve a goal, organizations are required to have competent human resources and are also experts in certain fields so that they are carried out properly and accurately. Based on the needs of the organization, human resources are needed who are trained and are in a place that is in accordance with their fields and expertise. This research was conducted at the Personnel, Education and Training Agency (BKP2D) of Indragiri Hulu Regency. The implementation of this study is expected for 8 (eight) months. This study was to determine the Effect of Training and Work Placement on Performance at the Personnel, Education and Training Agency (BKP2D) Kabupaten Indragiri Hulu. The analytical method used is descriptive quantitative data analysis carried out partially and simultaneously (multiple linear regression analysis with the help of IBM SPSS Statistics program version 23:00) The Result of regression is a positive relationship between training performance and there is also a positive relationship between work placement and performance. The results of the partial test had a significant effect on the performance of the training Personnel, Education and Training Agency (BKP2D) Indragiri Hulu Regency. Partial work placement has a significant effect on the Performance of Regional Personnel, Education and Training (BKP2D) Indragiri Hulu.